Entrepreneurship in Relation to the Competitive Potential and Position of Economies – a Regional Approach Based on Polish Provinces - Gawel , Aleksandra (Theory, Methodology, Practice – Review of Business and Management, 2014)
The aim of this study was to determine the influence of entrepreneurship on the competitiveness of regional economies, in particular on the competitive potential and position of regions. In order to do this, an empirical study of the Polish provinces was conducted. In order to achieve the aim of the study, regression function parameters were estimated by means of three methods: the classic method of least squares, the panel method with fixed effects and the panel method with random effects. Empirical confirmation was obtained for the first hypothesis, which assumed a positive impact of entrepreneurship on the competitive potential of a region. In particular, the findings lend support to the two related secondary hypotheses, which indicated a positive impact of the enterprise start-up rate (Hypothesis 1A) and enterprise density rate (Hypothesis 1B) on the competitive potential of a region. The issue of the impact of entrepreneurship on the competitive position of a region is less clear. One of the secondary hypotheses, which assumed a positive impact of the enterprise density rate on the competitive position (Hypothesis 2B) was confirmed by the findings. However, the enterprise start-up rate was found to have an adverse influence on the competitive position of regions, thus Hypothesis 2A has to be rejected.